Effects of glyphosate plus foliar manganese application on the production and quality of marandu grass - Codognoto, Luciane da Cunha; Conde, Thassiane Telles; Maltoni, Katia Luciene; Faria, Glaucia Amorim; Cavali, Jucilene (Acta Scientiarum. Animal Sciences, 2021)
In this study, the stimulatory effects of application of glyphosate herbicide coupled with manganese sulfate (8%) foliar fertilizer on the production and bromatological characteristics of Brachiaria brizantha ‘Marandu’ were evaluated. The experiments were performed using randomized complete block design with a 5×4 factorial scheme in plots subdivided over time (across four evaluations) with four repetitions, totaling 100 observations. The effects of sublethal doses of acid equivalent (a.e.) of glyphosate (5.40, 21.60, 64.80, and 108.00 g·a.e.·ha-1) and control plus manganese sulfate foliar fertilizer (1,000 g ha-1) were assessed in four successive evaluations at a defoliation frequency of 21 days. Foliage at 20 cm height (to evaluate forage production); leaf/stem ratio (LSR); and contents of crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), and lignin (LIG) were measured in experimental plots with a usable area of 7.5 m2. Application of sublethal doses of glyphosate plus manganese sulfate did not increase forage production, increased LSR, reduced LIG content, and did not affect CP content in all four evaluations. NFD and ADF indicated satisfactory qualitative indices for animal feed following the application of sublethal doses of glyphosate plus manganese sulfate in all four evaluations.